Nano material based on high-pressure shearing and preparation method thereof

By using high-pressure shear technology in the preparation of nanomaterials, the raw material powder is pretreated and high-pressure sheared, which solves the problems of uneven grain refinement, low efficiency and high energy consumption in the existing technology, and realizes efficient and environmentally friendly nanomaterial preparation, which is suitable for large-scale production.

CN119845672AActive Publication Date: 2025-04-18NINGBO UNIV
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411876758.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-04-18
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

The existing nanomaterial preparation methods have problems such as uneven grain refinement, low efficiency, and high energy consumption, which are difficult to be effectively applied in large-scale production.

Method used

Using a preparation method based on high-pressure shear, the formation of nano-scale grain structure is achieved by performing preliminary pretreatment of micron-scale raw material powder, and then applying axial pressure and rotary shear force in the high-pressure equipment to control the shear duration and total rotation angle.

Benefits of technology

It achieves efficient grain refinement, reduces energy consumption, simplifies operating procedures, is suitable for large-scale production, and improves the quality and performance of nanomaterials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119845672A_ABST
    Figure CN119845672A_ABST
Patent Text Reader

Abstract

The invention provides a nano material based on high-pressure shearing and a preparation method thereof, which are suitable for various powder raw materials, such as black phosphorus. According to the method, extremely high axial pressure is applied to high-pressure torsion equipment, rotational shear force is applied to a cross section, so that a powder material is violently crushed and refined under a high-pressure shear condition, and finally, a material with more refined grains is prepared. And carrying out high-pressure torsion treatment under the conditions of specific pressure, boosting speed and rotating speed. Experimental results show that by the adoption of the method, grains can be effectively refined, and the microstructure and the mechanical property of the material can be improved. Compared with a traditional preparation method, the preparation method has the advantages of being short in preparation period, simple in process, low in cost and the like, is suitable for large-scale production, can be applied to preparation of various nanometer materials, provides a new technical approach for efficient preparation of the nanometer materials, and has wide application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of nano material preparation, and in particular to a nano material based on high pressure shearing and a preparation method thereof. Background Art

[0002] Nanomaterials generally refer to a class of materials with a grain size between 1nm and 100nm. Due to their extremely small grain size and greatly increased number of grain boundaries, nanomaterials exhibit more excellent mechanical properties, including yield strength, hardness, toughness and fatigue resistance, and also show superior performance in optics, electricity, thermal and chemical stability. These characteristics of nanomaterials make them have broad application prospects in many fields such as electronic devices, energy storage, catalysis, and medicine. With the development of science and technology, the preparation and application of nanomaterials has become a hot topic of research.

[0003] In order to better prepare nanomaterials, people can effectively refine the grains of materials by improving traditional material processing techniques, such as severe plastic deformation in plastic forming technology, so as to prepare nanomaterials. This preparation method is not only simple in process and low in cost, but also easy to achieve large-scale production, providing strong support for the widespread application of nanomaterials. By combining severe plastic deformation with high pressure science, researchers have developed high-pressure torsion technology (HPT). As one of the typical large plastic deformation methods, high-pressure torsion technology causes severe plastic deformation of materials by applying high pressure and torsional force, that is, while axially compressing, a torque is applied on the cross section, thereby changing friction resistance into friction power, achieving a certain torsional deformation, and at the same time achieving grain refinement, uniform organization, fragmentation and redistribution of the second phase through simple compression deformation. For example, the original grains of the material are severely broken and refined to form a submicron fine-grained structure.

[0004] The microstructure and mechanical properties of the final sample of high pressure torsion technology (HPT) are mainly affected by a variety of process parameters such as aspect ratio, torsion angular velocity, extrusion speed, hydrostatic pressure, friction coefficient and temperature. The maximum shear strain value is closely related to the thickness, radius, pressure, number of rotations and rotation speed of the sample. Usually, the thickness and radius of the sample are determined during the preparation process, so the maximum shear strain value is determined by the pressure conditions, number of rotations and speed. The use of different parameters may cause significant changes in the material refinement effect and final performance. Specifically, if inappropriate process conditions are used, such as applying too high pressure or performing excessive number of rotations, not only can the nano-sizing of the material not be effectively promoted, but it may also aggravate the diffusion behavior of atoms and the migration rate of grain boundaries. This side effect directly accelerates the growth process of grains, which runs counter to the expected goal. On the contrary, if lower pressure and number of rotations are used, the grain refinement may not reach the nanoscale due to insufficient refinement of torsion deformation, resulting in poor refinement effect. Therefore, when preparing nanomaterials using high pressure torsion technology, the optimization and regulation of process parameters is crucial.

[0005] At present, the preparation methods of nano black phosphorus mainly include mechanical exfoliation, liquid ultrasonic exfoliation, electrochemical exfoliation, solvothermal method, chemical vapor deposition and ball milling. Although these methods have achieved certain results in the preparation of nanomaterials, they also have significant limitations. First, the reaction conditions of many methods are harsh, usually need to be carried out under the protection of inert gas, or require a specific high temperature and high pressure environment, which makes the process complicated and energy-intensive. Secondly, the existing methods are often prone to introduce impurities, and the organic solvents used may cause potential harm to the environment in some cases, which to a certain extent limits their scope of application and sustainability. In addition, most of these methods require the use of high-value raw materials and solvents, and involve a variety of complex chemical reactions and physical processes, requiring precise control of reaction conditions and experimental equipment, resulting in long production cycles and low efficiency, and difficult to be effectively applied in large-scale production.

[0006] Take black phosphorus as an example. As a relatively abundant element in nature, black phosphorus has three main allotropes: white phosphorus, red phosphorus and black phosphorus. Among these three allotropes, black phosphorus has attracted much attention due to its unique thermodynamic stability. Black phosphorus has a layered structure, each layer consists of two atomic layers and contains two different phosphorus-phosphorus bonds (PP bonds). This structural feature gives it unique physical and chemical properties. However, the traditional preparation process of black phosphorus faces many challenges, such as high difficulty in preparation and harsh preparation conditions, which limit the widespread application of black phosphorus. In recent years, scientists have successfully used mechanical exfoliation to prepare nanoscale black phosphorus and found that it has extremely high electron mobility. This discovery has opened up a new path for the research and application of black phosphorus. Compared with traditional black phosphorus, nanoscale black phosphorus has a larger specific surface area, more reactive sites and higher electron mobility, which makes nano black phosphorus have broad application prospects in many fields such as electronic devices, energy storage and biomedicine.

[0007] Although nano black phosphorus has broad application prospects, its efficient preparation remains a key issue that needs to be solved urgently. Although the existing methods for preparing nano black phosphorus have achieved some results in academic research, most methods still have the following problems: high energy consumption, harsh reaction conditions, long cycles and low efficiency. For example, although mechanical exfoliation and liquid ultrasonic exfoliation can produce high-quality nano black phosphorus, the process is complicated and energy-intensive, and these methods cannot be effectively applied in large-scale production. In addition, these methods are prone to introduce impurities during operation, affecting the quality of the final material. Therefore, it is urgent to develop a new preparation technology that can solve the defects in existing methods, improve preparation efficiency, and reduce energy consumption and environmental impact to meet the needs of large-scale production.

[0008] In summary, the prior art has many problems in the preparation process of nanomaterials, especially in terms of material quality control, process adjustability and industrial application. Therefore, it is an urgent problem to develop a nanomaterial preparation method that is efficient, environmentally friendly and has good industrial application prospects. The present invention arises at the historic moment under this background, and by adopting a new high-pressure shearing preparation technology, many defects in the prior art are successfully solved, providing a new solution for the efficient preparation of nanomaterials. Summary of the invention

[0009] The technical problem to be solved by the present invention is to provide a method for preparing nanomaterials based on high pressure shearing, so as to solve the problems of uneven grain refinement, low efficiency, complex processing process and high energy consumption existing in the conventional methods in the prior art.

[0010] In order to overcome the above defects of the prior art, the present invention provides a method for preparing nanomaterials based on high pressure shear conditions, comprising the following steps:

[0011] S1: Preliminary pretreatment of raw material powder with a particle size of micrometer level to improve the uniformity and processability of the raw material;

[0012] S2: pressing the pretreated raw material powder through a mold to form a sample block;

[0013] S3: Fill the gasket groove with the molded sample block and perform high-pressure shear treatment in a high-pressure device by applying axial pressure and constant torque, specifically including:

[0014] a: Apply shear force at a set rotation speed under axial pressure;

[0015] b: Control the shear duration and total rotation angle to refine the material grains and form a nano-scale grain structure;

[0016] Compared with the prior art, the nanomaterial preparation method based on high pressure shearing in this application has the following advantages:

[0017] Efficient grain refinement: Compared with traditional methods, the present invention avoids the problem of insufficient grain refinement in traditional methods by combining axial pressure and rotational shear force. Reduce energy consumption and improve efficiency: The present invention uses high pressure torsion (HPT) to subject the sample to shear deformation and high pressure shear, which not only improves the efficiency of material refinement, but also reduces dependence on high temperature environment and reduces energy consumption.

[0018] Simplified operation process: The sample processing process is simplified through unified high-pressure torsion. Compared with the complex chemical reaction steps in traditional methods, the process of the present invention is more direct and easy to control.

[0019] Suitable for large-scale production: Compared with existing nanomaterial preparation methods, the process of the present invention is simple, rapid and low-cost, and is particularly suitable for industrial production.

[0020] In a possible implementation, in step S1, the raw material powder is red phosphorus powder.

[0021] Compared with the existing technology, the above technical solution has unique advantages as a raw material, especially in the fields of electronics and energy storage. Its characteristics include: high electron mobility: black phosphorus has excellent electron conductivity, so that the nanomaterials prepared using black phosphorus powder as a raw material have superior performance in applications such as electronic devices and sensors; high specific surface area: black phosphorus has a large specific surface area, which helps to improve the reactivity and electrochemical properties of the material, and is particularly suitable for energy storage devices such as lithium batteries and supercapacitors; good chemical stability: black phosphorus is relatively stable under high temperature and humidity environments, and is suitable for a variety of harsh application environments; therefore, using black phosphorus powder as a raw material can improve the performance of the final nanomaterial in the fields of electronics and energy storage.

[0022] In a possible implementation, in step S1, the preliminary pretreatment includes: applying a pressure of 2-3 GPa to the raw material powder and maintaining the pressure for more than 15 minutes, and during the pressure maintenance period, heating the raw material powder to 700-800° C. and maintaining the temperature for 15 minutes.

[0023] Compared with the prior art, the above technical solution can pre-treat the structure of the raw material powder by applying a high pressure of 2-3GPa, promoting the stability and homogenization of its lattice. High pressure helps to improve the compactness of the powder and reduce the gaps between particles, making the subsequent high-pressure shearing treatment more efficient; heating the raw material powder to 700-800°C during the pressure holding process can promote the heat treatment reaction of the powder, accelerate the rearrangement of the grains and the homogenization of the material. The temperature increase helps to improve the physical properties of the powder, including plasticity, toughness, etc., thereby improving the processability and stability of the material during subsequent pressing and high-pressure shearing; the above possible implementation method homogenizes and stabilizes the grains of the raw material powder by applying high pressure and heating the raw material powder, thereby laying the foundation for the subsequent high-pressure shearing treatment, significantly improving the grain refinement effect of the nanomaterial, and improving the production efficiency and material performance. Compared with the prior art, this solution improves the efficiency of the preparation process through simple preliminary pretreatment, reduces energy consumption and time consumption, and is more suitable for industrial production.

[0024] In a possible implementation, in the step S1, the equipment used for the preliminary pretreatment is a six-sided top press.

[0025] Compared with the existing technology, the above technical solution can achieve efficient pressing and uniform distribution by applying uniform multi-directional pressure to the raw materials. Compared with the traditional unidirectional pressing method, the six-sided top press can apply pressure in multiple directions at the same time to ensure the uniformity and density of the powder. The equipment can better eliminate the gaps between particles and promote the homogenization and densification of grains.

[0026] In a possible implementation manner, in step S3, the axial pressure is mechanical oil pressure, and the mechanical oil pressure is 40-60 MPa, and the rotation speed is 720° / hour.

[0027] Compared with the prior art, the above technical solution applies an axial pressure of 40-60MPa, which can ensure that the sample is fully stressed during the high-pressure shearing process and promote the uniform refinement of the material grains. Moderate axial pressure helps the material to undergo drastic plastic deformation, thereby achieving effective grain refinement. If the applied pressure is too low, it may not effectively promote grain refinement; if it is too high, it may cause excessive material diffusion, which is not conducive to refinement; rotational shear force is one of the key operating parameters in the present invention. By setting a rotation speed of 720° / hour, a higher shear strain can be achieved, thereby effectively promoting the grain refinement of the material. Increasing the rotation speed can increase the frequency of the material being stressed, so that the shear force is more fully applied per unit time, promoting the crushing and homogenization of the grains. Too low a rotation speed may result in insufficient shear strain and inability to effectively refine the grains; too high a rotation speed may result in excessive plastic deformation of the material, affecting the stability of the subsequent material.

[0028] In a possible implementation, in step S3, the shearing duration is 0.5 hours, and the total rotation angle is 360°.

[0029] Compared with the prior art, the above technical solution is adopted to control the rotation angle of 360° during the high-pressure shearing process to ensure that the stress of the entire shearing area is evenly distributed when the sample is subjected to axial pressure. Under the action of the rotational shear force, the grains of the material undergo continuous and uniform deformation, which helps to achieve more detailed grain refinement. In each unit time, the increase in the rotation angle means the increase in the frequency of the sample being subjected to force, so that the shear stress can have a more continuous effect on the material, thereby accelerating the grain refinement process, and in the above embodiment of the present invention, the total rotation angle, the duration and the above axial pressure have a synergistic effect. The 360° rotation combined with the appropriate pressure and rotation speed can improve the grain refinement effect through synergy, and excessive rotation (greater than 360°) will cause the material to experience excessive shear strain, thereby causing the grains to be broken too fine. This will cause the grain size to be too small, which may damage the structural stability of the material, and even cause the grains to agglomerate or irregular in shape, thereby affecting the mechanical properties of the material; a small rotation angle may cause the material to experience insufficient shear strain, and cannot effectively promote grain refinement. The grain refinement effect may not be as expected, resulting in the microstructure of the material remaining unchanged or not refined enough. This means that the final material may not reach the nanoscale grain structure, reducing the performance of the material, and the problem of uneven grain refinement.

[0030] In a possible implementation, after step S3 is completed, step S4 verification is further included, which includes: S4: performing microstructural characterization on the sample after the high-pressure shearing treatment in step S3 to verify the grain refinement effect.

[0031] Compared with the prior art, the above technical solution can avoid excessive grain breakage while ensuring sufficient time by setting the shear duration to 0.5 hours. Within this time range, the material can fully receive the shear force, thereby achieving effective grain refinement, while avoiding the problem of excessive grain refinement or inhomogeneity caused by too long shear time; and setting the rotation angle to 360° means that the rotation force is applied evenly during the entire shearing process, which is crucial for the grain refinement of the material. The setting of the rotation angle ensures that the material is subjected to consistent shear stress throughout the process, which helps to uniformly refine the grains and effectively avoids grain inhomogeneity caused by local stress concentration.

[0032] In a possible implementation manner, in step S3, step S4 specifically includes: analyzing the grain size of the sample by X-ray diffraction test, combining the Scherrer formula Calculate the degree of grain refinement; photograph the samples using a scanning electron microscope, and perform statistical analysis on the sample grain size using Nano measurer software to further verify the grain refinement effect.

[0033] Compared with the prior art, the present invention adopts the above technical scheme, through XRD and Scherrer formula, combined with SEM and Nanomeasurer analysis, to achieve high-precision evaluation of grain refinement, ensuring that the nanomaterial reaches an ideal grain size and distribution during the preparation process. Through accurate grain refinement detection, process parameters can be adjusted in time during the preparation process to ensure stable and consistent quality of the final product. The grain refinement effect of the material is closely related to the performance (such as strength, conductivity, etc.), and accurate control and verification are helpful to improve the performance of the final product.

[0034] Another technical problem to be solved by the present invention is to provide a method for preparing nanomaterials by the above method, so as to solve the problems of uneven grains, unstable performance and many impurities existing in conventional nanomaterials in the prior art.

[0035] In order to overcome the above defects of the prior art, the present invention provides a nano material, which is prepared by the above method under high pressure shearing conditions.

[0036] Compared with the prior art, the nanomaterial of the present application has the following advantages: the nanomaterial of the present invention solves the problems of uneven grain refinement, high energy consumption and long production cycle in the existing nanomaterial preparation method by introducing high-pressure shearing technology, and ensures uniform grain refinement and high performance of the material by precisely controlling the shearing conditions, while improving production efficiency and reducing energy consumption. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 The X-ray diffraction patterns of the nano black phosphorus prepared in Example 1 of the present invention and the black phosphorus only after pretreatment;

[0038] Figure 2 The X-ray diffraction patterns of the black phosphorus prepared in the comparative example of the present invention and the nano black phosphorus in Example 1;

[0039] Figure 3 The cross-sectional scanning electron microscope image and grain size statistical graph of the raw material black phosphorus after pretreatment of the present invention;

[0040] Figure 4 The cross-sectional scanning electron microscope image and grain size statistical graph of the nano black phosphorus prepared in Example 1 of the present invention;

[0041] Figure 5 The cross-sectional scanning electron microscope image and grain size statistical graph of the nano black phosphorus prepared in the comparative example of the present invention;

[0042] Figure 6 The structure of the non-equilibrium high temperature and high pressure device R-PE100 used in the present invention and the schematic diagram of the force on the sample;

[0043] Figure 7 Schematic diagram of explosion of the non-equilibrium high temperature and high pressure device R-PE100 used in the present invention;

[0044] Figure 8 This is a schematic diagram of the assembly of the 3 mm anvil of the present invention;

[0045] Fig. 9 This is a schematic diagram of the force analysis of the sample of the present invention using ansys software;

[0046] Description of reference numerals:

[0047] Figure 8 In the figure, 1. anvil surface; 2. 3mm gasket; 3. sample. DETAILED DESCRIPTION

[0048] First, those skilled in the art should understand that these implementations are only used to explain the technical principles of the embodiments of the present application, and are not intended to limit the protection scope of the embodiments of the present application. Those skilled in the art can make adjustments to them as needed to adapt to specific application scenarios.

[0049] In the description of the embodiments of the present application, it should be noted that, unless otherwise clearly specified and limited, the terms "connected" and "connection" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be directly connected or indirectly connected through an intermediate medium. For ordinary technicians in this field, the specific meanings of the above terms in the embodiments of the present application can be understood according to specific circumstances. The MPa provided in the following implementation part and technical solution part of the present invention and the experimental conditions part is the machine oil pressure, and the corresponding anvil used is 3mm.

[0050] The present invention provides a method for preparing a nanomaterial based on high pressure shearing, comprising the following steps:

[0051] S1: Preliminary pretreatment of raw material powder with a particle size of micrometer level to improve the uniformity and processability of the raw material;

[0052] S2: pressing the pretreated raw material powder through a mold to form a sample block;

[0053] S3: Fill the gasket groove with the molded sample block and perform high-pressure shear treatment in a high-pressure device by applying axial pressure and constant torque, specifically including:

[0054] a: Apply shear force at a set rotation speed under axial pressure;

[0055] b: Control the shear duration and total rotation angle to refine the material grains and form a nano-scale grain structure;

[0056] As a preferred solution, in step S1, the raw material powder is red phosphorus powder.

[0057] As a preferred solution, in step S1, the preliminary pretreatment includes: applying a pressure of 2-3 GPa to the raw material powder and maintaining the pressure for more than 30 minutes, and during the pressure maintenance period, heating the raw material powder to 700-800°C and maintaining the temperature for 15 minutes.

[0058] As a preferred solution, in the step S1, the equipment used for the preliminary pretreatment is a six-sided top press.

[0059] As a preferred solution, in step S3, the axial oil pressure is 40-60 MPa, and the rotation speed is 720° / hour.

[0060] As a preferred solution, in step S3, the shearing duration is 0.5 hours and the total rotation angle is 360°.

[0061] As a preferred solution, after step S3 is completed, step S4 verification is also included, which includes: S4: performing microstructural characterization on the sample after the high-pressure shearing treatment in step S3 to verify the grain refinement effect.

[0062] As a preferred solution, in step S3, step S4 specifically includes: analyzing the grain size of the sample by X-ray diffraction test, combining the Scherrer formula Calculate the degree of grain refinement; photograph the samples using a scanning electron microscope, and perform statistical analysis on the sample grain size using Nano measurer software to further verify the grain refinement effect.

[0063] The invention also provides a nano material, and the nano material is prepared by the method under high-pressure shearing conditions.

[0064] Through the above-mentioned preparation method of nanomaterials based on high pressure shearing of the present invention, it is possible to effectively solve the problems of uneven grain refinement, low efficiency, high energy consumption, etc. in the prior art, and further improve the quality and production efficiency of nanomaterials, and provide strong support for the wide application of nanomaterials. The preparation method of nanomaterials based on high pressure shearing proposed by the present invention can efficiently prepare nanomaterials including nano black phosphorus, and compared with the conventional mechanical stripping method, liquid phase ultrasonic stripping method, electrochemical stripping method, solvent thermal method, chemical vapor deposition method and ball milling method, it has a shorter preparation cycle, a simpler experimental process, higher efficiency and lower cost. In addition, the requirements for experimental conditions are also more relaxed, which is more suitable for large-scale industrial production. The present invention provides a novel method for preparing nanomaterials based on high-pressure shearing, provides suitable experimental conditions and process flow, so that the grain refinement effect is optimized; the high-pressure torsion method of the present invention has simple method procedures, short experimental time, and high preparation efficiency; and the present invention can adopt a non-equilibrium high-temperature and high-pressure device (R-PE100) for production, which is expected to realize future industrial production and promote the large-scale production of nanomaterials; the experimental conditions for preparing nanomaterials are greatly optimized, with high reliability, success rate and good test repeatability, and more suitable for industrial production needs.

[0065] The following provides specific embodiments in combination with the above technical solution to further illustrate the technical solution of the present invention:

[0066] Embodiment 1:

[0067] This embodiment provides a nanomaterial based on high pressure shearing and a preparation method thereof, and the specific steps of the preparation method are as follows:

[0068] S1: Raw powder pretreatment

[0069] Take red phosphorus powder with a particle size of micrometer level and use a six-sided top press to perform preliminary pretreatment to obtain black phosphorus powder. The specific steps are: apply a pressure of 3.0GPa to the raw material powder and keep the pressure for 30 minutes. During this period, the raw material powder is heated to 750℃ and kept warm for 15 minutes to improve the uniformity and processability of the powder.

[0070] S2: Sample block forming

[0071] The pretreated black phosphorus powder is pressed into powder form by a mold to form a sample block.

[0072] S3: High-pressure shear treatment

[0073] The molded sample block was filled into the groove of the 3 mm gasket, and the gasket was placed in the corresponding groove of the anvil. Subsequently, a high pressure shear treatment was performed in a high pressure device (R-PE100), specifically including:

[0074] a. Apply 50MPa axial oil pressure and apply shear force at a set rotation speed of 720° / hour;

[0075] b. The shearing duration is controlled to be 0.5 hours and the total rotation angle is 360°, so that the material grains are refined and a nano-scale grain structure is formed.

[0076] S4: Verify the grain refinement effect

[0077] The microstructure of the samples after high pressure shear treatment is characterized. Specifically, it includes:

[0078] a. Analyze the grain size of the sample through X-ray diffraction (XRD) test, and calculate the degree of grain refinement in combination with Scherrer formula;

[0079] b. The samples were photographed using a scanning electron microscope (SEM), and the grain size of the samples was statistically analyzed using Nano measurer software to further verify the grain refinement effect.

[0080] Embodiment 2:

[0081] This embodiment provides a nanomaterial based on high pressure shearing and a preparation method thereof, and the specific steps of the preparation method are as follows:

[0082] S1: Raw powder pretreatment

[0083] Take red phosphorus powder with a particle size of micrometer level and use a six-sided top press to perform preliminary pretreatment to obtain black phosphorus powder. The specific steps are: apply a pressure of 2.5GPa to the raw material powder and keep the pressure for 30 minutes. During this period, the raw material powder is heated to 750℃ and kept warm for 15 minutes to improve the uniformity and processability of the powder.

[0084] S2: Sample block forming

[0085] The pretreated black phosphorus powder is pressed into powder form by a mold to form a sample block.

[0086] S3: High-pressure shear treatment

[0087] The molded sample block was filled into the groove of the 3 mm gasket, and the gasket was placed in the corresponding groove of the anvil. Subsequently, a high pressure shear treatment was performed in a high pressure device (R-PE100), specifically including:

[0088] a. Apply 40MPa axial oil pressure and apply shear force at a set rotation speed of 720° / hour;

[0089] b. The shearing duration is controlled to be 0.5 hours and the total rotation angle is 360°, so that the material grains are refined and a nano-scale grain structure is formed.

[0090] S4: Verify the grain refinement effect

[0091] The microstructure of the samples after high pressure shear treatment is characterized. Specifically, it includes:

[0092] a. Analyze the grain size of the sample through X-ray diffraction (XRD) test, and calculate the degree of grain refinement in combination with Scherrer formula;

[0093] b. The samples were photographed using a scanning electron microscope (SEM), and the grain size of the samples was statistically analyzed using Nano measurer software to further verify the grain refinement effect.

[0094] A comparative example is also provided below:

[0095] Comparative Example:

[0096] The difference between the comparative example and Example 1 is mainly that the total rotation angle is 720° and the processing time is also different.

[0097] S1: Raw powder pretreatment

[0098] The black phosphorus powder is pretreated using a six-sided top press. The specific steps are as follows:

[0099] S1: Apply a pressure of 2.5 GPa to red phosphorus powder with a particle size of micrometer level and maintain it for 30 minutes. During this period, the raw material powder is heated to 750°C and maintained at this temperature for 15 minutes to improve the uniformity and processability of the powder.

[0100] S2: Sample block forming

[0101] The pretreated black phosphorus powder is pressed into powder form by a mold to form a sample block.

[0102] S3: High-pressure shear treatment

[0103] The molded sample block was filled into the groove of the 3 mm gasket, and the gasket was placed in the corresponding groove of the anvil. Subsequently, a high pressure shear treatment was performed in a high pressure device (R-PE100), specifically including:

[0104] a. Apply 50MPa axial oil pressure and apply shear force at a rotation speed of 720° / hour;

[0105] b. The shearing duration is 1 hour, and the total rotation angle is 720°, which refines the material grains and forms a nano-scale grain structure.

[0106] S4: Verify the grain refinement effect

[0107] The microstructure of the samples after high pressure shear treatment is characterized. Specifically, it includes:

[0108] a. Analyze the grain size of the sample through X-ray diffraction (XRD) test, and calculate the degree of grain refinement in combination with Scherrer formula;

[0109] b. The samples were photographed using a scanning electron microscope (SEM), and the grain size of the samples was statistically analyzed using Nano measurer software to further verify the grain refinement effect.

[0110] Table 1: Statistics of strong peaks in raw materials of the present invention and Examples 1-2:

[0111]

[0112] As shown in Table 1, Table 1 is a statistical table of strong peaks of the raw material (black phosphorus powder) after pretreatment of the present invention and the nanomaterials prepared in Example 1 and the comparative example. Table 1 also summarizes Figure 1-2 Half-peak width of each strong peak;

[0113] like Figure 1-2 As shown, the X-ray diffraction patterns of the black phosphorus prepared in Example 1 and the comparative example of the present invention and the raw material black phosphorus after only the pretreatment in step S1; Figure 1 This is a cross-sectional scanning electron microscope comparison of the black phosphorus prepared in Example 1 of the present invention and the raw material black phosphorus;

[0114] Figure 3-4 They are respectively the scanning electron microscope images of the cross section and the grain size statistics of the raw material black phosphorus after pretreatment of the present invention and Example 1 of the present invention;

[0115] Figure 1The X-ray diffraction (XRD) comparison diagram of the pretreated black phosphorus raw material and nano black phosphorus is shown. This figure shows that the strength of the black phosphorus after high-pressure shearing treatment is greatly improved compared with the original black phosphorus, which further proves that the method of the present invention can effectively refine the raw material grains, increase the crystallinity of the material, and improve the ordered structure;

[0116] Figure 3-4 The cross-sectional SEM comparison diagram of the black phosphorus prepared in Example 1 of the present invention and the raw material black phosphorus is shown in the cross-sectional SEM diagram. The raw material black phosphorus is usually characterized by large and unevenly distributed particles, showing the characteristics of relatively rough grains and large particles. After the high-pressure shearing treatment, the black phosphorus grains are significantly refined, the particles are more uniform, the grain distribution is more dense, and a fine submicron grain structure is shown. This shows that the high-pressure shearing technology of the present invention effectively breaks the original grains of black phosphorus and promotes the uniform refinement of the grains.

[0117] Figure 4 The cross-sectional scanning electron microscope image and grain size statistical graph of the nano black phosphorus prepared in Example 1 of the present invention are shown. In Example 1, Figure 4 The grain size of the material was measured and counted to verify the effect of high-pressure shearing treatment on grain refinement. The details of the sample were photographed by scanning electron microscope (SEM), and the grain size was accurately analyzed and counted using Nano measurer software. The figure shows that the grain size of the material after high-pressure shearing treatment is significantly reduced, showing a trend of uniform refinement, which meets the requirements for the preparation of nanomaterials.

[0118] like Figure 2 and Figure 4-5 As shown, Figure 2 Table 1 is the X-ray diffraction diagram of the black phosphorus prepared in the comparative example of the present invention and the nano black phosphorus in Example 1; Figure 1-2 Statistical table of half-peak width values ​​of each strong peak in the Figure 4-5 The comparative examples of the present invention are respectively Figure 5 ) and the black phosphorus of Example 1, cross-sectional scanning electron microscopy and SEM grain size statistical comparison diagram;

[0119] Figure 2 The X-ray diffraction patterns of Example 1 and the comparative example are shown. Figure 2 It is known that since the rotation angle of the comparative example reaches 720 degrees, due to excessive rotation, its half-peak width becomes narrower, indicating that excessive rotation leads to excessive alignment of grains and structural optimization. Compared with the wide peak in Example 1, the grain refinement effect in Example 1 is more uniform and meets the requirements of nanomaterials. Therefore, excessive rotation may bring unnecessary changes in material structure and affect the final performance;

[0120] Figure 4-5A scanning electron microscopic comparison of the black phosphorus cross-section of the embodiment and the comparative example is shown, showing the cross-sectional structure comparison of the nano black phosphorus and the raw black phosphorus prepared in the embodiment 1 and the comparative example. It can be seen from the figure that the nano black phosphorus prepared in the embodiment 1 has a significantly refined grain structure, while the sample in the comparative example exhibits larger particles or grains. This further proves that after the sample in the embodiment 1 is treated with high-pressure shear, the degree of grain crushing is higher and the particle size is smaller, thereby improving the performance of the material, enhancing the hardness and other mechanical properties, while in the comparative example, due to the different processing time and rotation angle, the grain refinement effect of the material is not optimal, resulting in larger grains, thereby affecting the performance of the final nanomaterial. This further proves that the present invention further controls and selects the rotation reading and pressure energy parameters to play a synergistic role.

[0121] and Figure 4 In Example 1, the average particle size of the raw material is 0.01917 μm, and the grain size distribution is relatively concentrated, which indicates that the grains of the sample are relatively small and the fluctuation is not large; Figure 5 In (Comparative Example), under the treatment condition of 720 degrees, the grain size after treatment becomes significantly larger. The size of most grains is concentrated in a larger size range (between 0.05μm and 0.15μm), and the average size of the grains is 0.106μm. Compared with Example 1, the average value of the grain size after treatment has increased significantly, and the grains are more uneven, indicating that during the high-pressure shearing process, the grains have undergone greater stretching and shearing forces, which further proves the rationality of the 360-degree rotation of the present invention.

[0122] Figure 6-Figure 9 As shown, the specific equipment and stress conditions in Example 1 of the present invention are shown. Figure 6 The schematic diagram of the structure and force analysis of the high-pressure shearing device R-PE100 are shown, and the layout of the components inside the device is clearly visible, which is used to achieve the effective preparation of nanomaterials in the method of the present invention; Figure 7 This is the explosion diagram of R-PE100, through which we can clearly see the structure of each part of the device and further understand its working principle and experimental conditions under high pressure environment; Figure 8 This is a schematic diagram of the assembly of the 3 mm anvil of the present invention, which shows the assembly method of the 3 mm anvil, so that each sample in the experimental process can be treated uniformly. Figure 8 Including: 1. anvil surface; 2. 3mm gasket; 3. sample; Fig. 9 Figure 9 is a schematic diagram of the stress analysis of the sample of the present invention using ANSYS software. The stress analysis is performed using ANSYS software, which shows in detail the deformation process of the sample under different pressure conditions, helping to understand how these mechanical effects affect the grain structure of the material, thereby achieving a higher level of grain refinement.

[0123] In the description of the embodiments of the present application, it should be noted that in the description of the present application, terms such as "inside" and "outside" indicating directions or positional relationships are based on the directions or positional relationships shown in the drawings. This is only for the convenience of description, and does not indicate or imply that the device or component must have a specific orientation, be constructed and operated in a specific orientation. Therefore, it cannot be understood as a limitation on the present application.

[0124] In the description of the present application, the description with reference to the terms "one embodiment", "some embodiments", "in the present embodiment", "specific example", or "some examples" etc. means that the specific features, mechanisms, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, mechanisms, materials or characteristics described may be combined in a suitable manner in any one or more embodiments or examples. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0125] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application shall be based on the protection scope of the claims.

Claims

1. A method for preparing nanomaterials based on high pressure shearing, characterized in that: The following steps are involved: S1: Preliminary pretreatment of raw material powder with a particle size of micrometer level to improve the uniformity and processability of the raw material; S2: pressing the pretreated raw material powder through a mold to form a sample block; S3: Fill the gasket groove with the molded sample block and perform high-pressure shear treatment in a high-pressure device by applying axial pressure and constant torque, including: a: Apply shear force at a set rotation speed under axial pressure; b: Control the shear duration and total rotation angle to refine the material grains and form a nano-scale grain structure.

2. The method for preparing nanomaterials based on high pressure shearing according to claim 1, characterized in that: In the step S1, the raw material powder is red phosphorus powder.

3. The method for preparing nanomaterials based on high pressure shearing according to claim 1, characterized in that: In the step S1, the preliminary pretreatment includes: applying a pressure of 2-3 GPa to the raw material powder and maintaining the pressure for more than 30 minutes, and during the pressure maintenance period, heating the raw material powder to 700-800° C. and maintaining the temperature for 15 minutes.

4. The method for preparing nanomaterials based on high pressure shearing according to claim 3, characterized in that: In the step S1, the equipment used for the preliminary pretreatment is a six-sided top press.

5. The method for preparing nanomaterials based on high pressure shearing according to claim 1, characterized in that: In the step S3, the axial pressure is a mechanical oil pressure, and the mechanical oil pressure is 40-60 MPa, and the rotation speed is 720° / hour.

6. The method for preparing nanomaterials based on high pressure shearing according to claim 5, characterized in that: In step S3, the shearing duration is 0.5 hours, and the total rotation angle is 360°.

7. The method for preparing nanomaterials based on high pressure shearing according to claim 1, characterized in that: After the step S3 is completed, the step S4 verification is also included, which includes: S4: performing microstructural characterization on the sample after the high-pressure shearing treatment in the step S3 to verify the grain refinement effect.

8. The method for preparing nanomaterials based on high pressure shearing according to claim 7, characterized in that: In step S3, step S4 specifically includes: analyzing the grain size of the sample by X-ray diffraction test, combining the Scherrer formula Calculate the degree of grain refinement; photograph the samples using a scanning electron microscope, and perform statistical analysis on the sample grain size using Nano measurer software to further verify the grain refinement effect.

9. A nanomaterial, characterized in that: The nanomaterial is prepared by the method according to any one of claims 1 to 8 under high pressure shearing conditions.

Citation Information

Patent Citations

  • Metal material surface layer structure ultra-refining treatment method

    CN103695617A

  • Method for preparing graphene by using high-pressure homogenizer delamination

    CN105540575A

  • Method for high-temperature ultrahigh-pressure preparation of flaky platinum selenide

    CN106431407A

  • Preparation method of phosphorus / porous carbon / graphene composite material

    CN108767209A

  • ZL107 aluminum alloy gradient material and preparation method thereof

    CN113789488A